1993
DOI: 10.1177/030089169307900201
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomas Involving the Abdominal and Pelvic Cavity

Abstract: The principles of management of all sarcomas that involve the abdominal and pelvic cavity are presented. The anatomic sites for the primary malignancy include retroperitoneal sarcomas, pelvic side-wall sarcomas, sarcomas arising from the abdominal viscera, and sarcomas arising from the pelvic organs. All histologic types of sarcomas may be considered together when therapeutic options are being discussed. This presentation stresses surgical removal with an adequate margin of resection as the principal goal of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Frequently, patients with pelvic soft tissue sarcoma are included in studies of patients presenting with sarcoma at other anatomical sites [5,17]. Other reviews of pelvic soft tissue sarcoma grouped with retroperitoneal sarcoma have suggested that outcome is poor in these patients, even when intensive therapy such as intra-operative radiation is utilized [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequently, patients with pelvic soft tissue sarcoma are included in studies of patients presenting with sarcoma at other anatomical sites [5,17]. Other reviews of pelvic soft tissue sarcoma grouped with retroperitoneal sarcoma have suggested that outcome is poor in these patients, even when intensive therapy such as intra-operative radiation is utilized [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Important prognostic factors for STS include size, grade, metastasis, and resection margin [1,2,4±8]. Retroperitoneal and pelvic STS have been noted for large size at presentation [2,5,7], extracompartmental extension [4,8], high grade [2], and dif®culty in obtaining wide surgical resection margins [6,7,9±14]. Various methods of treatment for pelvic STS have been described and include nonsurgical management [3], piecemeal excision [5], wide resection [3], internal hemipelvectomy [2], and hindquarter amputation [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…No data are available about the effect of radiotherapy in small bowel LMS. Furthermore, LMSs have a very low response rate to chemotherapy (23,24). Therefore, metastasectomy, if possible, should be considered (5,8,25).…”
Section: Treatmentmentioning
confidence: 99%
“…Sarcomas arise from mesoderm-derived elements anywhere in the body, with the lower extremities being the most common site. 1,2 Over the course of the past several decades, a multimodality treatment approach has significantly improved the quality of life and survival for patients with extremity sarcomas. Unfortunately, patients with abdominal sarcomas have not experienced such improvements and continue to have an extremely high rate of recurrence and poor overall survival.…”
mentioning
confidence: 99%
“…Unfortunately, patients with abdominal sarcomas have not experienced such improvements and continue to have an extremely high rate of recurrence and poor overall survival. [1][2][3][4][5][6] Despite aggressive surgical resection, with or without adjuvant systemic chemotherapy, the vast majority of these patients succumb to uncontrolled intraperitoneal sarcomatosis. [1][2][3][4][5][6][7][8][9][10][11] The intraperitoneal dissemination of certain sarcomas is very similar to that of ovarian cancer.…”
mentioning
confidence: 99%